Interannual Variability of Methane Storage and Emission During Autumn Overturn in a Small Lake. Issue 12 (3rd December 2021) - Ragg, R. B.; Peeters, F.; Ingwersen, J.; Teiber‐Siessegger, P.; Hofmann, H.
Abstract: Methane emissions from freshwater systems, and especially from small lakes, source a significant proportion of naturally produced atmospheric methane. In small temperate lakes, storage flux, that is, the diffusive emission of methane that was stored in anoxic waters during the seasonal overturn of the water column, can contribute a large fraction of annual methane emissions. Here, we use an extensive field data set to quantify methane storage in anoxic deep water and identify as well as quantify the sources and losses of this methane. The comparison of measurements from 4 years in a small temperate lake (Illmensee) shows that methane storage can differ substantially between years. In 2012 and 2018, the annual maximum of the methane stored in the entire water column was around twice as high (5, 350 and 5, 822 kg) as in 2013 and 2017 (2, 722 and 2, 295 kg). A methane mass balance approach suggests that the variability of methane storage in the anoxic water between the years was not caused by the methane flux at the anoxic–oxic water interface, but rather was related to changes in the methane source from the anoxic sediments. The interannual differences in sediment flux could not be explained by sediment temperature, but rather by the differing supply of organic matter. Our findings suggest that phytoplankton blooms promote methane storage within the same year and thus cause interannual variability in emissions during autumn overturn. Plain Language Summary: Methane emissions from lakes are a major natural source of atmospheric methane. Small, temperate lakes that form an anoxic deep water layer during stratified conditions can store huge amounts of methane that can be suddenly released to the atmosphere during overturning. Our study provides evidence that and why within a lake methane storage and emission during autumn overturn can differ substantially between years. The interannual variability is affected not only by the overturn dynamics but also by the stored mass of methane at the end of the stratification period. The latter is strongly linked to the autochthonous primary production during that period for two reasons: the degraded biomass (a) affects the duration and extent of anoxic conditions in the deep water and thus the duration of methane accumulation and the area of the sediment surface at which methane fluxes from sediments are not oxidized and (b) leads to an increase in methane production and therefore in the source of methane in anoxic waters. Thus, ecosystem productivity and its interannual variability are major modulators of methane emissions from lakes. In consequence, lakes that experience higher nutrient loadings and climate warming are expected to increase their contribution to global methane emissions. Key Points: The stored mass of methane at the end of the stratified period is strongly linked to the autochthonous primary production during the season The interannual variability of methane emissions during overturn is mainly triggered by the seasonal magnitude in primary production Climate warming and higher nutrient loadings are expected to increase the contribution of lakes to global methane emissions